Naskah lama daerah Jawa Timur Kunjara Karnna (Proyek Pengembangan Media Kebudayaan, Departemen Pendidikan dan Kebudayaan, 1977)
Romanization and Indonesian translation of one of the known Kawi palm leaf manuscripts of Kuñjarakarṇna; includes commentary.